STRATEGI PEMBERDAYAAN MASYARAKAT PESISIR DI KABUPATEN KEPULAUAN MERANTI - Tampubolon, Dahlan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
The study was to identify and formulate strategies for theempowerment of coastal communities in Kabupaten Meranti Islands.SWOT analysis is a main method. Using SWOT analysis, evaluatedthe internal and external factors affecting empowerment. Potentialcoastal communities consist of fisheries and agriculture sectors. Thisarea has the potential for great fisheries resources with high spirit offishermen.